Research on the relationship between carbon performance and financial performance of electric power enterprises under the background of “dual carbon” - He, Jiajun; Huang, Zirui; Fan, Xin; Zhang, Hui; Song, Mingwei; Zhao, Yiming; Zhang, Chenzhi (Frontiers in Environmental Science, 2024)
Under the background of “dual carbon,” the power industry, as a pillar industry of the national economy, is ushering in changes. Based on the data of listed companies in the electric power production and supply industry from 2010 to 2020, this paper takes the operating income corresponding to each unit of carbon emission as the substitute variable of carbon performance (CP). After dimensionality reduction of 12 financial indicators through factor analysis, this paper establishes a comprehensive indicator of financial performance (FP), and establishes panel data to explore the relationship between CP and FP of electric power enterprises. To mitigate the endogeneity problem, 2SLS regression was performed using instrumental variables. The results show that CP has a positive and sustainable impact on the FP, which indicates that power enterprises need to pay attention to the long-term management of carbon emission reduction, so that the improvement of FP of enterprises can achieve sustainable development, which is in line with the expectations of Porter’s hypothesis and stakeholder theory. In addition, firm size plays a negative moderating role in the relationship between CP and FP. The research results provide a path and basis for encouraging power enterprises to improve CP and help China achieve the goal of “dual carbon” as soon as possible.